How Mechanics Shaped the Modern World - Allen, David H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This unique book presents a nontechnical view of the history of mechanics, from the Big Bang to present day. The impact of mechanics on the evolution of a variety of subjects is vividly illustrated, including astronomy, geology, astrophysics, anthropology, archeology, ancient history, Renaissance art, music, meteorology, modern structural engineering, mathematics, medicine, warfare, and sports. While enormous in scope, the subject matter is covered (with ample photographic support) at a level designed to capture the interest of both the learned and the curious. The book concludes with a creative and thoughtful examination of the current state of mechanics and possibilities for the future of mechanics. This book also: Presents an offbeat, nontechnical chronology of the history of mechanics, from the Big Bang to present day Lays out a complicated scientific subject in a rapid-fire narrative that is both interesting and informative for the non-specialist reader Covers subjects ranging from Egyptian civilization, music and musical instruments, art, and climate dynamics and demonstrates how their evolution both impacted and was impacted by humankind's understanding of mechanics Thoughtfully examines the current state of mechanics and possibilities for future research and innovation
Mechanics and Our Ancestors -- The Greeks -- The Romans -- Mechanics in the Middle Ages -- The Artistic Renaissance -- Finding Our Way -- Mechanics Reborn -- Music and Measuring -- Continua, Art and Structures -- Weather -- Life Cycles -- The Quality of Our Lives -- Mechanics Today -- The Future of Mechanics.
Keywords: Engineering; Science -- History; Mechanics; Mechanics, applied; Engineering; Theoretical and Applied Mechanics; History of Science; Mechanics